ANALYSIS OF THE IMPLEMENTATION OF TAX ACCOUNTING FOR FIXED ASSETS IN. ALKESINDO BUANA CAKRA - ZULIA HANUM; RAIESA AMIN (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to analyze the application of tax accounting on fixed assets at PT. Buana Alkesindo Chakra is in accordance with tax regulations and to find out how they apply to these fixed assets. Fixed assets that are used to support the company's operational activities have considerable value. So that fixed assets are a fairly important component in financial statements and can influence the decision making of a financial statement that is presented and also affect the calculation of a company's taxable income. The data obtained in the study came from primary and secondary data with qualitative and quantitative data types. Data collection techniques used in this study are documentation studies, namely to obtain secondary data and interviews that are used to obtain primary data. The data analysis technique used is qualitative descriptive analysis. Based on the results of the study, there were errors in grouping fixed assets for economic life and the rates used by PT. Cakra Buana Alkesindo in calculating depreciation of fixed assets. The company also does not record the acquisition of fixed assets or when depreciation of fixed and improper assets at presentation in the financial statements. So that the value of the taxable income is not as it should be, because the depreciation expense of the asset is still higher than what is expected by the company.